Association between dry eye symptoms and suicidal ideation in a Korean adult population. - Sun-Bi Um; Hyungseon Yeom; Na Hyun Kim; Hyeon Chang Kim; Hyung Keun Lee; Il Suh (PLoS ONE, 2018)
Purpose This study assessed the association of dry eyes with depression and suicidal ideation in a Korean adult population. Methods Data from 16408 participants (6972 men and 9436 women) aged ≥ 19 years included in the fifth Korea National Health and Nutrition Examination Survey, conducted from 2010-2012, were analyzed. For dry eyes, surveys of previous diagnosis of dry eye disease (DED) by an ophthalmologist and experience of subjective dry eye symptoms were separately used. Diagnosis of depression and suicidal ideation were obtained via responses to an interviewer-assisted questionnaire, and questions were asked in a closed-ended response format. Logistic regression was used to examine the associations between dry eyes, depression, and suicidal ideation. Results DED diagnosis exhibited an odds ratio (OR) of 1.32 (95% confidence interval [CI] 1.11-1.57) for depression and 1.24 (95% CI 1.05-1.48) for suicidal ideation compared to those without DED, after adjusting for sex, age, education, occupation, household income, body mass index, smoking behavior, alcohol consumption, physical activity, hypertension, diabetes, dyslipidemia, thyroid diseases, major cardiovascular disease, and cancer. Similarly, the adjusted OR (95% CI) of dry eye symptoms was 1.50 (95% CI 1.30-1.73) for depression and 1.47 (95% CI 1.27-1.70) for suicidal ideation. Conclusion Our findings suggest that dry eyes (either DED diagnosis or dry eye symptoms) may be associated with the prevalence of depression and suicidal ideation in the Korean adult population.